HTTP blocking in CN: instagram.com, twitter.com, whatsapp.com, youtube.com (China) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in China. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0006. Severity: warning. Confidence: 85%